Analisis Persediaan Stok Barang Warung Menggunakan Data Mining Dengan Algoritma Fp-Growth (Studi Kasus: Warung Bu Nani) - Annisa Siti Habibah; Arip Solehudin; Aji Primajaya (Peneliti.net, 2022)
Shop Bu Nani discusses how to stock stall items using the FP-Growth Algorithma. This kiosk stock data is used to find out what stock items are empty. The use of the FP-Growth Algorithm to determine the stock of kiosk goods. The use of FP-Tree which is used in conjunction with the Fp-Growth Algorithm to determine the Frequent Itemset of a database. The Association Rule method is used to find patterns of interest in lapak stock products in policy making. So that it can be seen which stall stock is empty, based on the rules generated from the data contained in the database. This test was performed using RapidMiner Studio Tool Version 9.10. The results obtained from the test are the smaller the support value, the greater the number of items produced and the more rules formed